Report of Working Group on Legal, Institutional and Financing Aspects - Planning Commission (Planning Commission, 1999)
The terms of reference for the Working Group on 'Legal, Institutional and Financing Aspects' are given in Annexure - 2. Of the twenty five terms of reference, a few have also been studied by the other Working Groups. The report presented in the following paras does not discuss the items in the terms of reference one by one. They are taken together and though the report is written under three distinct heads- the legal, institutional and financing aspects, the items in the terms of reference are covered in one para or another.
Government of India Ministry of Water Resources New Delhi September, 1999
Planning Commission
Keywords: Legal Issues; Institutional Aspects; Financing Aspects; River Boards Act; Inter-State Water Disputes; Inter Basin Transfer of Waters; Inter-State Sharing of Waters; The Proposed River Basin Organisation; Water Rights; Matters Relating to Ground Water Regulation